Identification of Arthropod Diversity in The Cemara Beach Mangrove Ecosystem - Yulianti Yulianti; Munawir Sazali (International Journal of Science, Technology and Applications, 2025)
Mangrove ecosystems play an important role in maintaining the balance of the coastal environment and become a habitat for various types of fauna, including arthropods. This study aims to identify the types of arthropods and determine the level of diversity in the mangrove ecosystem of Cemara Beach, West Lombok Regency. The method used is an exploratory survey method with sampling techniques using Hand Collecting and Sweep Netting in several mangrove vegetation zones.  The presence of these arthropods suggests that the mangrove ecosystem in Cemara Beach still supports the life of various small organisms, although some environmental changes, such as deforestation and increased garbage are beginning to affect the presence of some species. Therefore, the results of this study can be the initial basis for sustainable mangrove conservation and management efforts, while affirming the importance of the role of arthropods in maintaining the balance of coastal ecosystems.